Eficacia del romero (rosmarinus officinalis) en la inhibición de cándida álbicans - Montúfar Guachilema, María Fernanda (2019)
Due to the antifungal properties attributed to rosemary (rosmarinus officinalis) described in the literature, the aim of this study was to compare the inhibitory efficacy of the aqueous extract and rosemary essential oil on Candida Álbicans, one of the causative agents of subprosthetic stomatitis . Once obtained the 10 percent aqueous extract and the pure essential oil of rosemary the evaluation of its antifungal properties was carried out against C. Álbicans (strain ATCC 102130), by means of the microdilution technique in broth, in which two microtitre plates were used plastic cups (Thermo Scientific) of 96 wells each, within which the microdilution of the 10 percent aqueous extract and rosemary essential oil was carried out in the study inoculum (C. Álbicans) on the Mcfarland scale 0.5, using as control positive Clotrimazole at 2 percent, the microtubules were incubated at 37 degrees celsius for 24 hours, the readings were made with the Bio-Tek-Sinergy spectrophotometer at 1 hour, 3 hours and 24 hours. Results: the pure essential oil and 10 percent aqueous extract of rosemary did not completely inhibit the formation of colonies of C. álbicans, however when performing the statistical analysis it was obtained that, the essential oil of Romero is 25.9 percent more effective than the aqueous extract.